Absence of paraneoplastic antineuronal antibodies in sera of 145 patients with motor neuron disease. Issue 8 (21st February 2007) - Stich, Oliver; Kleer, Barbara; Rauer, Sebastian
Abstract : Background: Well characterised antineuronal antibodies (ANAbs) have been shown to be highly specific markers of neurological syndromes with a paraneoplastic aetiology. Previous reports indicate that pure motor neuron disease (MND) is rarely of paraneoplastic origin. Objective: To screen systematically for the prevalence of well characterised paraneoplastic ANAbs in a large collective of patients with pure MND. Methods: In a cohort of 145 patients with MND, the frequency of ANAbs was estimated by ELISA, employing recombinant antigens (HuD, Yo, Ri, CV2/CRMP5, Ma2 and amphiphysin). Results: None of the sera revealed high antineuronal antigen reactivity. Very low reactivity was detected in only five sera, in all probability representing background activity. Conclusion: According to these data, routine analysis for ANAbs in patients with isolated MND is not mandatory.